Inovasi Publikasi Ilmiah Berbasis Digital: Strategi Ketahanan LPPJPHKI UNIVED Bengkulu Di Era Kewirausahaan Digital (Kwudig) - Vettyca Diana Saputri; Karona Cahya Susena; Anzori Anzori (Jurnal Bisnis, Manajemen dan Akuntansi, 2026)
Digital entrepreneurship (Kwudig) is no longer limited to the business sector but has become a crucial strategy for academic institutions to foster innovation and strengthen resilience in the digital transformation era. This study aims to describe how the Institute for Scientific Publication and Journal Management (LPPJPHKI) of Universitas Dehasen (UNIVED) Bengkulu applies the principles of digital entrepreneurship in developing technology-based scientific publications. Using a descriptive qualitative approach, the research was conducted through observations of the digital publication system and the journal marketing strategies implemented through various social media platforms. The findings indicate that LPPJPHKI UNIVED Bengkulu has successfully integrated digital innovation and entrepreneurial spirit through the management of the website publikasi-jurnal.id, the use of social media for promotion, and the implementation of an adaptive management system. These efforts have established a model of institutional resilience based on efficiency, innovation, and value creation within the digital entrepreneurship era.